PENGARUH PROFITABILITAS, LEVERAGE, INVESTMENT OPPORTUNITY SET DAN CORPORATE SOCIAL RESPONSIBILITY (CSR) TERHADAP NILAI PERUSAHAAN DENGAN KEBIJAKAN DIVIDEN SEBAGAI VARIABEL INTERVENING (STUDI PADA PERUSAHAAN SEKTOR PARIWISATA DI BURSA EFEK INDONESIA - Yuari Ade Sasmana Siregar; Yulia Efni; Rasuli Rasuli (JURNAL ECONOMICA: Media Komunikasi ISEI Riau, 2023)
This research aims to examine the influence of profitability, leverage, IOS and CSR on company value with dividend policy as an intervening variable. The population of this research is all Tourism, Hotel and Restaurant Sub-Sector Companies listed on the Indonesia Stock Exchange in 2016-2021. The statistical tool used in this research uses the structural equation modeling (SEM) method based on Partial Least Square (PLS) with the help of SmartPLS 4.0. From the results of this research it can be concluded that profitability influences dividend policy and company value, but profitability does not mediate company value through dividend policy. Leverage has no effect on dividend policy and company value and dividend policy does not mediate company value through dividend policy. IOS influences dividend policy and company value and dividend policy mediates IOS on company value through dividend policy. CSR has an effect on dividend policy and not on company value and also dividend policy does not mediate CSR on company value through dividend policy.